2013
DOI: 10.1590/s2317-17822013000300005
|View full text |Cite
|
Sign up to set email alerts
|

O uso da Classificação Internacional de Funcionalidade, Incapacidade e Saúde para acompanhamento de pacientes usuários de Implante Coclear

Abstract: This study concluded that most of the participating children showed no deficiency in the body functions, with difficulties being only reported in relation to school performance. Environmental factors (noise, non-availability of technological resources, absence of speech therapy) were characterized as a barrier. The need to expand assessments in the clinical routine was also noted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 12 publications
(10 reference statements)
1
4
1
5
Order By: Relevance
“…With respect to the Body Functions component, almost half of the pre-selected categories were contemplated in this study. This number was higher than those found in other reviews and original articles previously published, with respective selection of two (12) , three (13) , seven (8) , and twelve (14) categories. Other studies found a larger number of categories: seventeen (15) and thirty (16) .…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…With respect to the Body Functions component, almost half of the pre-selected categories were contemplated in this study. This number was higher than those found in other reviews and original articles previously published, with respective selection of two (12) , three (13) , seven (8) , and twelve (14) categories. Other studies found a larger number of categories: seventeen (15) and thirty (16) .…”
Section: Discussioncontrasting
confidence: 69%
“…Among the categories selected in the present study, the ones that were most frequently described in previous studies were those related to hearing functions (b230) (8,14,15,17) , specific mental functions (b140) (8,16) , (b144) (8,16) , (b156) (14,15) , and voice functions (b310) (13,15) .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…An Australian study highlights the great value of including the family in the process of counseling and clinical intervention, such as speech-language pathology (13) . For the authors, family members are aware of the impact that difficulties have on children and adolescents -an important factor to be considered in the definition of the priorities of therapeutic follow-up and to minimize parents' anxiety and frustration, which corroborate the findings of this research.…”
Section: Discussionmentioning
confidence: 99%
“…The national literature that makes use of the ICF-CY is scarce, and one of the first publications (13) in the field of Speech-Language Pathology based on the ICF-CY is aimed at children with cochlear implants and presents important questions for audiological practice.…”
Section: Introductionmentioning
confidence: 99%